School Climate and Student Mobility. Issue 4 (2nd October 2022) - Pogodzinski, Ben; Cook, Walter; Lenhoff, Sarah Winchell; Singer, Jeremy
ABSTRACT: School choice has been accompanied by an increase in student mobility. Although changing schools can benefit students, mobility is often associated with negative student and school outcomes. This study sought to better understand the relationship between school climate and the likelihood of student mobility across K-8 schools in Detroit, a city marked by a high level of school choice options. We found conflicting evidence of a relationship between measures of school climate as measured by the 5Essentials survey and student mobility. We discuss these findings in the context of potential sector differences, which may overshadow parental preferences for organizational characteristics.